Fractional Order Differential Equation In Banach Algebra (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In this paper, we investigate the fractional order nonlinear quadratic differential equation with initial value condition in Banach algebras under existence of solution. The primary conclusion is established using basic hybrid fixed point theory methods for three operators under certain monotonicity criteria.